Determinants of HAZ score in children under five in Glagah, Lamongan, Indonesia: A SEM-PLS analysis - Al Ayubi, Moch Thoriq Assegaf; As'ad, Muhammad; Ariyanti, Fajar (Public Health of Indonesia, 2023)
Background: Stunting is a nutritional condition of children with a Height for Age Z-score (HAZ score) under -2. The percentage of stunting in Indonesia in 2018 for children under five years of age was 30.80%, which has consistently increased since 2000. Glagah is a subdistrict in Lamongan Regency, which includes the national priority of the stunting intervention program. A multisectoral and comprehensive intervention must be related to evidence-based and previous relevant research and framework. However, there are various results about the determinants of stunting. Objective: This study aimed to identify direct and indirect effects from the determinant of HAZ score in children under five years of age in Glagah, Lamongan, Indonesia. Methods: This research employed a case-control design with K=2 and utilized a modified research questionnaire to collect the data. The population was mothers with 6–59-month-old children in Glagah. The samples were 88 control and 44 cases. The analysis was performed with SEM-PLS analysis with bootstrapping using α 0.05. Results: Our model shows an R-square of 0.433. Variables with the most affecting factors are Energy intake → HAZ (β 0.541), Protein intake → HAZ (β -0.327), Parenting score → HAZ (β 0.309), parenting score → energy intake (β 0.411), parenting score → protein intake (β 0.435), parenting score → energy intake → HAZ (β 0.222). Conclusion: These results provide an essential brief for community empowerment to increase parenting quality in a stunting intervention program. This research proposes an improvement on the environment and population variables for further study.